Risk Factors for Diabetes Mellitus in Patients with Pulmonary Tuberculosis: A Review - Hardianto; Wa Ode Salma; Jafriati; La Ode Muuhammad Sety; Asriati; Asnia Zainuddin (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Pulmonary tuberculosis (PTB) remains a significant global health problem, particularly in middle- and low-income countries. The comorbidity of TB and Diabetes Mellitus (DM) is increasing as both conditions influence each other through immunological and metabolic mechanisms. Chronic hyperglycemia in DM can impair immune function, thereby increasing susceptibility to mycobacterium tuberculosis infection and worsening TB treatment outcomes. Objective: This study aims to identify and analyze the risk factors contributing to the incidence of Diabetes Mellitus in patients with pulmonary Tuberculosis based on the latest scientific evidence from the past five years. Method: This study uses a Systematic Literature Review (SLR) approach guided by PRISMA. The articles analyzed were obtained from various scientific databases (Google Scholar, PubMed, Scopus, ResearchGate, and ScienceDirect) within the last five years (2020–2025). The keywords used include: Diabetes Mellitus, Pulmonary Tuberculosis, Risk Factors, and Comorbidities. The data were analyzed descriptively to identify similarities and differences in results among the studies. Results: A total of ten articles that met the inclusion criteria showed that advanced age, obesity, poor nutritional status, a family history of diabetes mellitus (DM), and irregular glycemic control are dominant factors that increase the risk of DM in pulmonary TB patients. Low socioeconomic status, unhealthy lifestyle, and low education levels also exacerbate the risk of TB-DM comorbidity. Results from various studies indicate that patients with DM have longer TB treatment durations, higher relapse rates, and lower cure rates compared to patients without DM. Conclusion: The relationship between pulmonary TB and diabetes mellitus is reciprocal and complex, involving biological, social, and behavioral factors. An integrated control approach is needed through dual screening, nutritional education, blood glucose management, and cross-sector collaboration to reduce incidence rates and improve treatment success for TB-DM in the community.